Literatura Infantil Negra: a relevância da articulação texto-imagem para uma educação antirracista - Fernandes, Raquel Duarte (2021)
This study aims to identify specificities of the verb-visual articulation Black Children's Literature books focusing on anti-racist education. In a specific way, it seeks to verify in analyzed books aspects that value black culture and possible contributions that these books can offer for an anti-racist education. This research is justified by the poor adherence to the Law nº 10.639 / 2003, which requires the teaching of Afro-Brazilian History and Culture in elementary and high schools in Brazil (Brazil, 2004); the need to adopt a decolonizing perspective; the importance of representativeness of black children in literature, in a country made up of different ethnic and cultural roots like Brazil; for considering the adoption of an anti-racist stance in research and education to be essential and, finally, for collaborating with future studies developed about Black Children's Literature. The analyzes and the theoretical reference are based on Candido (1988), Amarilha (2013) and Zilberman’s (2008) studies about literature; Cademartori (2008) and Faria’s (2004) considerations about illustrations; Ramos and Nunes (2013) and Fittipaldi’s (2008) perceptions about the verb-visual relation; Martins and Cosson’s (2008) ideas about Black Children's Literature and Almeida’s (2019) racism concept. Linked to the project “Black Children's Literature: debating the color of silence in the classroom” (AMARILHA, 2018 - 2022 [CNPq-UFRN]), this research is exploratory and bibliographic. The corpus consists of eight Black Children's Literature books: Pedro Noite, by Caio Riter (2011); Chico Moleque, by Maria Luiza Bretas (2016); O jovem caçador e a velha dentuça, by Lucílio Manjate (2016); O Casamento da Princesa, by Celso Sisto (2009); Ombela: a origem das chuvas, by Ondjaki (2018); Iemanjá e o poder da criação do mundo, a tale from the book Omo-Oba: histórias de princesas, by Kiusam de Oliveira (2009); Okpija, a tale from the book Ulomma: a casa da beleza e outros contos, by Sunny (2011); Abraçados no mato da Guiné, by Heloisa Lima, from the book Amores em África, organized by Lenice Gomes (2017). The criterion for selecting the books were: being recent; easy to access; have black characters; have articulated illustrations to the verbal text. The books analyzed show the relevance of multimodal text for discussion of ethnic-racial issues, considering that images present the physical attributes of characters while the verbal text develops the plot. Thus, it becomes unnecessary to show through words the ethnicity of characters, naturalizing this aspect, which contributes to implement an education that opposes racism, prejudice and discrimination.